Optimization of School Financing Management Based on Islamic Boarding Schools in The Era of The Independent Curriculum - Nugroho, Murwanto Setyo; Suyatmini; Astuti, Dwi Setyo (CV. Publikasi Indonesia, 2024)
An educational institution carrying out educational activities cannot be separated from financing. Quality financing management will maintain the continuity of learning activities. This research aims to dig deeper into efforts to optimize financing management for Islamic boarding school-based schools in the Independent Curriculum era. The research location is at Asy-Syifa Sukoharjo Boarding School Junior High School, which is one of the boarding-based schools in Sukoharjo. With a qualitative descriptive research approach, research data was obtained through interviews, observation, and document review. The research results reveal that education financing management can be optimized. RAPBS implements a priority system created by analyzing previous RAPBS and audit team reports in more depth. Entrepreneurship programs are based on local potential and investment to prepare education funds. Effective and efficient use of funds with periodic audits and applying technology-based reporting. Evaluation of the use of funds as a whole (holistic) from stakeholders and the community increases the accuracy of the allocation of education funds in order to achieve the goals of providing education in the Independent Curriculum era.